Embodied carbon transfers and employment-economic spillover effects in China’s inter-provincial trade - Yang, Dewei; Guo, Ruifang; O’Connor, Patrick; Zhou, Tian; Zhang, Shuai; Meng, Haishan; Wan, Min; Dai, Chunyan; Ma, Weijing (Frontiers in Environmental Science, 2023)
Embodied carbon transfers in interprovincial trade and their economic-employment spillover effects are the reference benchmark for low-carbon economic transition and equity management. Surprisingly, few studies have focused on the intrinsic relationship between embodied carbon, embodied GDP, and embodied employment in interprovincial trade and its equity implications. Based on multi-regional input-output tables for 2012 and 2017, our study of inter-provincial trade in 30 Chinese provinces shows that: (1) net outflows of embodied carbon were concentrated in the Beijing-Tianjin region and the eastern and southern coastal regions, while net inflows were in the central and northwestern regions; (2) embodied carbon, GDP, and employment were characterized by nearby transfer, complementary energy economy, and asymmetric transfers in and out; and (3) the internal relationship between net transfers of embodied carbon, GDP, and employment suggests that western provinces, which rely heavily on traditional energy and heavy chemical industries, gain a competitive disadvantage. To mitigate the inequity of inter-provincial carbon trade, top-down climate goals must be aligned with bottom-up socio-economic incentives to achieve balanced regional development and improved public welfare.